Socialization of BPJS Participation in National Health Insurance (JKN) Program as an Effort to Achieve Universal Health Coverage in Perbarakan Village, Deli Serdang Regency - Sirait, Reni Aprinawaty; Sumantri, Bambang; Kasim, Felix; Kurnia, Anggia; Br Ginting, Luci Riani (JURNAL PENGMAS KESTRA (JPK), 2024)
Universal Health Coverage (UHC) is a global commitment to ensure that all people have access to quality health services without facing financial hardship. In Indonesia, the National Health Insurance (JKN) program managed by BPJS Kesehatan aims to provide protection and benefits of health services, including promotive, preventive, curative, and rehabilitative services. However, challenges related to public understanding of this program are still significant. Based on observations in Perbarakan Village, Deli Serdang, the majority of people have minimal knowledge about JKN. Therefore, community service activities in the form of counseling were designed to improve their understanding of JKN. Socialization activities were carried out in Perbarakan Village, Deli Serdang Regency, involving 50 participants in the format of lectures, discussions, and questionnaire distribution. The pretest results showed low public knowledge about the JKN program, with only 35% of participants knowing basic information. After being given education, there was a significant increase in the post-test results, with 100% of respondents answering correctly, recording a 65% increase in knowledge. In addition, understanding of the procedure for moving primary health facilities increased by 48%.These findings suggest that clear and structured education can increase public awareness and understanding, which in turn supports the achievement of UHC goals. Therefore, appropriate and sustainable socialization is essential to ensure active community participation in the JKN program, so that it can expand access and utilization of quality health services. This counseling is expected to encourage public awareness to register as JKN participants, strengthen health protection, and support the achievement of UHC in Indonesia.